Tacrolimus trough and dose intra‐patient variability and CYP3A5 genotype: Effects on acute rejection and graft failure in European American and African American kidney transplant recipients. Issue 12 (31st October 2018) - Seibert, Stephan R.; Schladt, David P.; Wu, Baolin; Guan, Weihua; Dorr, Casey; Remmel, Rory P.; Matas, Arthur J.; Mannon, Roslyn B.; Israni, Ajay K.; Oetting, William S.; Jacobson, Pamala A.
Abstract: Background: Suboptimal immunosuppression after kidney transplantation contributes to toxicity and loss of efficacy. Little is known regarding the impact of intra‐patient variability of tacrolimus (TAC) doses and troughs in the early post‐transplant period or the influence of genetic variants on variability. Methods: Coefficients of variation (CV) of TAC troughs and doses of 1226 European American (EA) and 246 African American (AA) adult recipients enrolled in DeKAF Genomics were compared for association with acute rejection and graft failure. Additionally, the influence of recipients' number of CYP3A5 loss‐of‐function alleles was assessed. Results: Acute rejection was associated with greater CV of dose in AA ( P < 0.001) and EA recipients ( P = 0.012). Graft failure was associated with a greater CV of dose ( P = 0.022) and trough ( P < 0.001) in AA, and higher CV of trough ( P = 0.024) in EA recipients. In EA, CYP3A5 loss‐of‐function alleles were associated with decreased CV of trough ( P = 0.0042) and increased CV of dose ( P < 0.0001). Conclusion: CYP3A5 loss‐of‐function alleles influence intra‐patient TAC trough and dose variability. High variability of TAC dose increases risk of acute rejection. High variability of TAC trough increases risk of graft failure. Early clinical recognition of TAC dose and trough variability may improve patient management and outcomes.